Development Strategy Of Hygienic Fish Marketing In Samudera Fishing Port of Bitung - Resya Ika Firmansyah; Rene Charles Kepel; Suria Darwisito; Rose O.S.E. Mantiri; Vivanda O.J. Modaso; Deiske A. Sumilat; Suzanne L. Undap (Sam Ratulangi University, 2020)
Hygienic Fish Marketing (HFM) is one of the functional facilities at the fishing port provided to facilitate the marketing of fishery products. The right development strategies of HFM must take into account the potential, opportunities, constraints, and problems. The objectives of this research are (1) to determine the condition of utilization percentage analysis of fish resources landed at HFM and to analyze the level of facility utilization at HFM, and (2) to arrange strategies and recommendations for the development of HFM at PPS Bitung. The research method used to analyze catch prediction data for the next 10 years was arithmetic analysis. Analysis of utilization percentage was used to find out the level of facility utilization at HFM. Analysis of the development strategy of HFM at PPS Bitung used SWOT matrix analysis and QSPM analysis. The projection of fish catch landed over the next 10 years will increase by 24.77% per year, which is predicted to be 83,549.40 tons in 2029. The level of facility utilization is categorized as good with a value of 71.22%, that utilization level of HFM runs optimally. Based on the analysis using the SWOT matrix and QSPM analysis, it was found that the priority strategies are the main choices in the development of HFM at PPS Bitung which increase the operational capacity of loading docks and port ponds.Keywords: TPI hygienic, Development Strategy, Internal, and External FactorAbstrakTPI Higienis merupakan salah satu fasilitas fungsional di pelabuhan perikanan yang disediakan untuk memfasilitasi kegiatan pemasaran hasil perikanan. Strategi pengembangan TPI Higienis yang tepat harus memperhitungkan potensi, peluang, kendala, dan permasalahan. Tujuan dalam penelitian ini yaitu (1) mengetahui kondisi sumberdaya ikan yang didaratkan di TPI Higienis dan menganalisa tingkat pemanfaatan fasilitas di TPI Higienis dan (2) menyusun strategi dan rekomendasi pengembangan TPI Higienis PPS Bitung. Metode penelitian yang digunakan untuk menganalisa data prediksi hasil tangkapan selama 10 tahun kedepan adalah analisa aritmatik. Untuk mengetahui tingkat pemanfaatan fasilitas TPI Higienis, digunakan analisis persentasi pemanfaatan. Analisa strategi pengembangan TPI Higienis PPS Bitung menggunakan analisa matriks SWOT dan analisa QSPM. Proyeksi hasil tangkapan yang didaratkan selama 10 tahun kedepan mengalami kenaikan sebesar 24,77% pertahun sehingga pada tahun 2029 produksi diprediksi sebesar 83.549,40 ton. Tingkat pemanfaatan fasilitas masuk dalam kategori baik dengan nilai 71,22% sehingga tingkat pemanfaatan TPI Higienis berjalan optimal. Berdasarkan hasil analisa menggunakan matrik SWOT dan analisa QSPM didapatkan prioritas strategi yang menjadi pilihan utama dalam strategi pengembangan TPI Higienis di PPS Bitung yakni meningkatkan kapasitas operasional dermaga bongkar dan kolam pelabuhan.Kata kunci: TPI Higienis, Strategi Pengembangan, Faktor Internal dan Eksternal